(untitled) (Nonconventional Technologies Review, 2020)
The strategic management of an innovative organization is the process in which managers establish long term orientation, propose performance objectives, develop strategies for achieving the objectives in accordance with the factors involved, internal and external. The external environment defines the vicinity of innovative organization and consists of those elements that directly influence it and over which it can exert a significant influence. In parallel with the analysis of external environment, the organization must carry out an assessment of commercial, productive, innovative, financial, organizational and human potential. Thus, it is possible to determine its ability to deal with threats and capitalize on opportunities. The analysis of external and internal environment must be followed by the construction of scenarios that represent an adequate solution by elaborating a set of alternatives of future of innovative organization that could materialize. The SWOT analysis of innovative organization evaluates the strengths and weaknesses of internal environment, respectively the opportunities and threats from the external environment.